Effect of low temperature vacuum annealing on microstructural, optical, electronic, electrical, nanomechanical properties and phase transition behavior of sputtered vanadium oxide thin films. (24th October 2016) - Porwal, Deeksha; Esther, A Carmel Mary; Dey, Arjun; Gupta, A K; Kumar, D Raghavendra; Bera, Parthasarathi; Barshilia, Harish C; Bhattacharya, Manjima; Mukhopadhyay, Anoop Kumar; Khan, Kallol; Sharma, Anand Kumar
Abstract: Vanadium oxide thin films were deposited on quartz substrate by pulsed RF magnetron sputtering technique at 400–600 W and subsequently annealed at 100 °C in vacuum (1.5 × 10 −5 mbar). Phase analysis, surface morphology and topology of the films e.g., both as-deposited and annealed were investigated by x-ray diffraction, field emission scanning electron microscopy and atomic force microscopy techniques. X-ray photoelectron spectroscopy (XPS) was employed to understand the elemental oxidation of the films. Transmittance of the films was evaluated by UV–vis-NIR spectrophotometer in the wavelength range of 200–1600 nm. Sheet resistance of the films was measured by two-probe method both for as-deposited and annealed conditions. XPS study showed the existence of V 5+ and V 4+ species. Metal to insulator transition temperature of the as-deposited film decreased from 339 °C to 326 °C after annealing as evaluated by differential scanning calorimetric technique. A significant change in transmittance was observed in particular at near infrared region due to alteration of surface roughness and grain size of the film after annealing. Sheet resistance values of the annealed films decreased as compared to the as-deposited films due to the lower in oxidation state of vanadium which led to increase in carrier density. Combined nanoindentation and finite element modeling were applied to evaluate nanohardness ( H ), Young's modulus ( E ), von Mises stress and strain distribution. Both H and E were improved after annealing due to increase in crystallinity of the film.